Risk of self-injurious behavior increases in adolescence: new findings - Quiroga-Garza, Angélica; Ochoa Vera, Fátima; de la Garza Chapa, Ana Lucía; Ibarra Almaguer, Paola Abigail; Becerra Pérez, Elisa; Hernández Hernández, Mariana; Durán Treviño, Ana Gabriela (Frontiers in Psychology, 2025)
IntroductionSelf-injurious behaviors are a type of self-inflicted violence, with or without suicidal intentions. Approximately 10% of the global population has exhibited non-suicidal self-injury (NSSI); in Mexico, these behaviors are most common among individuals aged 10–29, with an average onset age of 12.3 years in Nuevo León.ObjectiveTo determine the predictive power of childhood traumatic events, emotional dysregulation, peer social pressure, and digital social networks on the incidence of self-injurious behaviors in adolescents aged 11–16 who are part of the educational system in the metropolitan area of Nuevo Leon, Mexico.MethodsA quantitative, non-experimental, cross-sectional, explanatory study was conducted. Six measurement questionnaires were used including a Screening of Self-injurious Behaviors and Suicide Related with Internet Use for adolescents designed by the authors for this study. For statistical analyses, we were considered ratio or continuous variables. The correlation was carried out using Spearman's rank coefficient and a significance level of 95% was applied to determine the predictive value of each variable on self-injurious behaviors and/or suicidal ideation.ResultsA high prevalence of the self-injurious behaviors and suicide ideation among adolescents, highlighting not only traditional risk factors like emotional dysregulation, peer pressure, and childhood trauma but also the significant impact and predictive value of digital exposure to content about self-harm and suicide in social digital networks.ConclusionNot all adolescents fully recognize the severity of their own behaviors or their peers' behaviors, which can lead to delays in seeking help. There is a need for prevention efforts, such as psychoeducation and open communication, alongside regulation of harmful content on social media. To address the problem holistically, collaboration between parents, educators, and health professionals is recommended.